Influence of sex over infant mortality at the Hermanos Cordové Hospital between 2000 and 2019 - Guillermo Manuel Figueredo Montero; Juan David Santaelena Berro; Claudia Amalia Cuevas Rodríguez; Suzanne Santiesteban Puerta; Yordan Álvarez Rondón; Claudett Mauren Álvarez San Miguel (Universidad de Ciencias Médicas de Granma, 2023)
Introduction: the infant mortality rate is an indicator of quality of life, the most widely used on an international scale to assess the development of the health status achieved in a population. Infant mortality rate according to sex, are available for the first time in the report of the World Health Organization since 2011, showing male predominance. Objective: to describe the influence of sex on infant mortality at the "Hermanos Cordové" hospital during the period 2000-2019. Method: an observational, longitudinal, retrospective, descriptive study was carried out. The study population was made up of 69 deceased under one year in the institution during the reference period. The gender variable was evaluated. The statistical method used was the frequency distribution on a qualitative scale: percentages, ratio and rates. The crude global and punctual mortality rate was calculated. Result: the male sex prevailed with 56.8%. The crude infant mortality rate by sex was 1.94 children per 100 live births. Ratio of 1.7 males for each female. Conclusion: the male sex has had a negative influence on the results of infant mortality in the "Hermanos Cordové" hospital during the last 20 years.